Risk factors for neural tube defects in the war and siege-affected tigray regional state of ethiopia: a case-control study - Birhane Alem Berihu; Afework Mulugeta; Tony Magana; Tafere Gebreegziabher Belay; Peixin Yang; Hayelom Kebede Mekonen (BMC Pregnancy and Childbirth)
Abstract Background Neural tube defects (NTDs) remain a significant global health concern, with varying prevalence and risk factors across regions. In Tigray, the war and siege have severely disrupted healthcare services, exacerbating pregnancy complications and increasing NTD prevalence. This study investigates the sociodemographic, obstetric, and conflict-related risk factors contributing to NTDs in Tigray during the crisis. Methods A case-control study was conducted between December 2023 and January 2024, including 103 NTD cases and 205 controls. Data were collected using a WHO-adapted birth defect survey and ODK/KOBO software. Statistical analysis was conducted using SPSS version 27, with descriptive statistics used for participant characteristics and logistic regression models applied to identify risk factors for neural tube defects, using a significance threshold of p < 0.05. Result A total of 308 participants were included (103 NTD cases and 205 controls). Stillbirths accounted for 79.7% of NTD cases, with anencephaly as the most common defect, followed by spina bifida and encephalocele. Among NTD cases, 23.3% were male, 18.4% female, and 58.3% had unidentified sex. Associated congenital anomalies were less common, including hydrocephalus (2.9%), clubfoot, omphalocele, and cleft palate (1-1.9%). Key risk factors for NTDs included younger maternal age, low education, history of abortion or stillbirth, and lack of prenatal care. Conflict-related factors, such as violence, unintended pregnancies, and limited healthcare, worsened NTD prevalence. Food insecurity was found a significant issue, with many women relying on aid or subsistence farming and consuming fewer than two meals per day. Conclusion The study demonstrates that neural tube defects, particularly anencephaly the most frequently observed subtype are strongly associated with increased stillbirth rates. Diagnostic challenges, including high rates of unidentified fetal sex and low detection of associated anomalies, coupled with limited prenatal care and maternal sociodemographic factors, contribute to poor prognoses. The ongoing conflict in Tigray has further worsened maternal health risks through healthcare disruptions, increased violence, unintended pregnancies, and food insecurity, potentially contributing to the higher prevalence of neural tube defects. These findings underscore the urgent need for strengthened maternal healthcare systems, targeted prevention strategies, and improved access to care, particularly in conflict-affected regions.